GEOCHEMISTRY AND NATURE OF THE PROTOLITH OF LOWER PROTEROZOIC Fe-Al METAPELITES IN THE TRANSANGARA REGION, YENISEI RIDGE - Vershinin A.E.; Likhanov I.I.; Reverdatto V.V. (My University, 2007)
Numerous facts and evidence in support of the essentially isochemical character of metamorphism opened wide the possibility for deciphering the primary nature of metamorphic rocks. One of the most efficient methods for reconstruction of the protolith and geodynamic settings of its formation is analysis of REE patterns and indicator ratios between other trace elements. These methods are widely applied in studying magmatic and sedimentary rocks, but less often used for metamorphic rocks because of a lack of data on the trace element distribution. Up to now, only limited data have been available on REE distribution in Fe–Al pelites, the metamorphism of which produces rare mineral assemblages of chloritoid, Fe-cordierite, and other minerals.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой